Factors associated with completeness of basic immunization for babies at Simpangkatis health center in 2023 - Monica; Harmendo; Muhammad Fahd Asmaruddin (BEMAS: Jurnal Bermasyarakat, 2024)
The Simpangkatis Health Center is located in Simpangkatis Village, Simpangkatis District, Central Bangka Regency, Bangka Belitung. Immunization is very important for children's development and can prevent various dangerous diseases and disabilities such as chicken pox, polio, tuberculosis, and others. Based on data obtained from 2019 to 2022 for completeness of basic immunization in Central Bangka Regency, it can be concluded that completeness of basic immunization is still low. Central Bangka regency, especially at the Simpangkatis Community health Center, the completeness of immunization is still low every year. The aim of this research is to find out what is related to the completeness of basic immunization for babies at the Simpangkatis Health Center, Central Bangka Regency in 2023 because the data obtained shows that the fulfillment of complete basic immunization is quite low. This research method was carried out using analytical methods with a cross sectional study design. The data collection method used a questionnaire sheet and was carried out in September 2023. The sample for this research was 91 people. The results obtained showed that the mother's education level (p=0,025), mother's level of knowledge (p=0,024), mother's employment status (p=0,021), and family support (p=0,074). The conclusion is that there is a significant relationship between the level of maternal education, the level of maternal knowledge, and the mother's employment status with the completeness of basic immunizations for babies, while for family support there is no relationship with the completeness of basic immunizations for babies at Simpangkatis Health Center in 2023